"They Stood like Men": Horses, Myth, and Carnophallogocentrism in Toni Morrison's Home. (28th June 2021) - Alonso-Recarte, Claudia
Abstract: Toni Morrison's fiction has frequently attracted critical attention on account of her strategic use of myth (whether classical or Afrocentric) and symbols. This paper examines the role that horses have, as rhetorical constructs, in strengthening the mythical and symbolic unity of her tenth novel Home (2012). Horses have figured widely in the articulation of African American history and letters, often serving as symbols of the abused slaves upon whose bodies the equipment and instruments of oppression and bondage were violently placed. Within Morrison's cornucopia of animal imagery, their presence is essential for an understanding of the rituals that are so much a part of the novel's exploration of masculinity and the overcoming of trauma. The horses in Home stand as mythopoetic agents around whom the problematic completion of rituals revolves. As namely linguistic constructs, the rhetorical devices and choices employed in the description of the horses and their final fate points to a discourse that signifies on the structural tensions that are characteristic of classical mythology but that also draw on the African American communal experience. At the same time, they invite a reading of Morrison's ritualistic pulse through Jacques Derrida's carnophallogocentric schema. The schema links together the different motifs and interspecies similes and metaphors that populate the text, enabling a deconstruction of the "centaur" image that lies at the heart of the protagonist's homecoming journey